2011
DOI: 10.1038/ejhg.2011.215
|View full text |Cite
|
Sign up to set email alerts
|

Skewed X inactivation and survival: a 13-year follow-up study of elderly twins and singletons

Abstract: In mammalian females, one of the two X chromosomes is inactivated in early embryonic life. Females are therefore mosaics for two cell populations, one with the maternal and one with the paternal X as the active X chromosome. A skewed X inactivation is a marked deviation from a 50:50 ratio. In populations of women past 55-60 years of age, an increased degree of skewing (DS) is found. Here the association between age-related skewing and mortality is analyzed in a 13-year follow-up study of 500 women from three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Differently from some authors [ 12 ] but similar to others [ 11 ], we did not find any association between inactivation and symptomatic status or neurological scores. We observed a trend relating an increased skewing with age, which is in accordance with literature [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…Differently from some authors [ 12 ] but similar to others [ 11 ], we did not find any association between inactivation and symptomatic status or neurological scores. We observed a trend relating an increased skewing with age, which is in accordance with literature [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, in elderly individuals, this ratio may be skewed. During a 13-year follow-up it was recently shown that this skewing is associated with survival [26]. It remains to be established whether this skewing has an influence on the expression of immune-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several of the genes regulating oxidative stress and inflammatory response are found on the X chromosome . During a woman's lifetime, cells with a nonfunctioning X‐chromosome gene expression are downregulated, and cells with more potent gene expression are retained . In addition, estrogen diminishes oxidative stress and stimulates the transcription of the gene encoding the telomerase reverse transcriptase enzyme that adds telomere repeats .…”
Section: Discussionmentioning
confidence: 99%